A Robust Phenotypic High-Throughput Antiviral Assay for the Discovery of Rabies Virus Inhibitors - Xinyu Wang; Winston Chiu; Hugo Klaassen; Arnaud Marchand; Patrick Chaltin; Johan Neyts; Dirk Jochmans (Viruses, 2023)
Rabies virus (RABV) causes severe neurological symptoms in mammals. The disease is almost inevitably lethal as soon as clinical symptoms appear. The use of rabies immunoglobulins (RIG) and vaccination in post-exposure prophylaxis (PEP) can provide efficient protection, but many people do not receive this treatment due to its high cost and/or limited availability. Highly potent small molecule antivirals are urgently needed to treat patients once symptoms develop. In this paper, we report on the development of a high-throughput phenotypic antiviral screening assay based on the infection of BHK-21 cells with a fluorescent reporter virus and high content imaging readout. The assay was used to screen a repurposing library of 3681 drugs (all had been studied in phase 1 clinical trials). From this series, salinomycin was found to selectively inhibit viral replication by blocking infection at the entry stage. This shows that a high-throughput assay enables the screening of large compound libraries for the purposes of identifying inhibitors of RABV replication. These can then be optimized through medicinal chemistry efforts and further developed into urgently needed drugs for the treatment of symptomatic rabies.